2021
DOI: 10.1128/mbio.01891-21
|View full text |Cite|
|
Sign up to set email alerts
|

Secondary Metabolites from Food-Derived Yeasts Inhibit Virulence of Candida albicans

Abstract: The gut microbiome, primarily established by food, is complex and contributes to the health of the host. Molecular mechanisms that regulate microbial interactions and host health remain unclear.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In this study, we have observed that aromatic alcohols exhibit inhibitory effects on the growth of S. cerevisiae in high concentrations, reaching several grams per liter, as shown in Figure 1 . Under normal conditions, yeast are incapable of producing these alcohols in such significant quantities, with growth media typically accumulating only 0.01–0.02 g/L of phenylethanol, tyrosol, and tryptophol ( Zupan et al, 2013 ; Kunyeit et al, 2021 ). Meanwhile, overexpression of individual ARO genes can increase the concentration of tyrosol to approximately 0.05 g/L ( Bisquert et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have observed that aromatic alcohols exhibit inhibitory effects on the growth of S. cerevisiae in high concentrations, reaching several grams per liter, as shown in Figure 1 . Under normal conditions, yeast are incapable of producing these alcohols in such significant quantities, with growth media typically accumulating only 0.01–0.02 g/L of phenylethanol, tyrosol, and tryptophol ( Zupan et al, 2013 ; Kunyeit et al, 2021 ). Meanwhile, overexpression of individual ARO genes can increase the concentration of tyrosol to approximately 0.05 g/L ( Bisquert et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that pretreatment of Lb21 lactic acid bacteria could not only increase the lifespan through increasing the resistance to pathogenic methicillin‐resistant Staphylococcus aureus , and Lb21‐mediated MRSA resistance mainly acted on the DBL‐1 ligand in the TGF‐β signaling pathway (Mørch et al, 2021). Kunyeit et al (2021) found that food‐derived beneficial yeasts could regulate and protect the C. elegans , make them less damaged by Candida albicans and prolong their lives, providing new ideas for the treatment of fungal infections (Kunyeit et al, 2021). ML1206, which has 99% similarity with the marine Planococcus maritimus , was screened as a potential marine probiotic acting for the infection of C. elegans by Vibrio anguillarum .…”
Section: Application Of C Elegans Model To Evaluate Nutrition Of Acti...mentioning
confidence: 99%
“…These genes include HSP150 and YGP1 , which regulate responses to stress and acidic pH tolerance; HSP26 and SSA4 , which regulate heat responses; and ARO9 and ARO8 , which are involved in the biosynthesis of aromatic alcohols, such as phenylethanol and tryptophol [ 41 , 42 ]. These aromatic alcohols can inhibit the virulence of C. albicans [ 43 ]. Moreover, S. boulardii has been reported to secrete medium-chain fatty acids, mainly capric acid, with bioactivity against C. albicans hyphae and biofilm formation [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%